Bone Mineral Density (BMD) in Women with Helicobacter Pylori (HP) Induced Chronic Gastritis in Comparison with Healthy Women - AA Abravesh (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Osteoporosis and bone fracture consequence to it is an important cause of disability particularly in the elderly women. Identifying the causes of osteoporosis and its treatment is important in fracture prevention. The present study was parformed to determine the relationship between helicobactor pylori infection (HP) and ostoporosis in the women.METHODS: In this cross sectional study, forty-two women with clinical features of dyspepsia due to HP– induced chronic gastritis confirmed by gastroscopy and biopsy were compared with 52 healthy control women without dyspepsia. Bone mineral density (BMD) was assessed by dual energy x-ray absorptiometry (DXA). Femoral neck BMD gr/cm2 and spine BMD gr/m2 were compared between whole number of two groups as well as between patients and controls according to age. FINDINGS: The mean age of patients and controls were 51.6± 9.2 and 51.7± 6.5 years, respectively. There were no significant differences in mean spine and femoral neck BMD between the whole numbers of patients and controls. But in groups aged 50 and /=50 years with those aged < 50 years demonstrated a significant difference only in patients for spine BMD (p=0.017) but not in the controls.CONCLUSION: These findings indicate that HP-induced inflammation has no adverse effect over femoral neck BMD but has negative effect on spine BMD in women aged >/=50 years. Further studies with larger samples are needed to confirm these findings.